A comparative study of the efficacy of a porcine reproductive and respiratory syndrome subunit and a modified-live virus vaccine against respiratory diseases in endemic farms - Oh, Taehwan (Can J Vet Res, 2019)
The efficacy of a porcine reproductive and respiratory syndrome (PRRS) subunit vaccine was evaluated and compared with a modified-live virus (MLV) vaccine under field conditions. Three farms were selected based on their history of respiratory diseases caused by co-infection with both PRRSV-1 and PRRSV-2. In each farm, 60 pigs were randomly allocated to 2 vaccinated and 1 unvaccinated groups (20 pigs per group). One group of pigs were administered the PRRS subunit vaccine at 21 and 42 days of age and another group administered the PRRS MLV vaccine at 21 days of age. The subunit vaccine had similar efficacy and, in some instances, performed even better than the MLV vaccine. Vaccination of pigs with either of the PRRS vaccines resulted in significantly improved growth performance in Farm B but not in Farm C. In Farm A, pigs vaccinated with the PRRS subunit vaccine had a better growth performance statistically compared to those vaccinated with the PRRS MLV vaccine. At the peak of PRRSV-1 and PRRSV-2 viremia, neutralizing antibodies and T-cell responses against PRRSV-1 and PRRSV-2 were at low levels suggesting that either vaccine is only able to provide a partial protection against co-circulating PRRSV-1 and PRRSV-2.